Keadaban Digital dan Etika Tauhid: Telaah Kritis Filsafat Pendidikan Muhammadiyah dalam Era Literasi Artifisial - Herdiana Mulyono; Sudarnoto Abdul Hakim; Zamah Sari (Jurnal Kajian Ilmiah, 2025)
The advancement of digital technology and the emergence of artificial intelligence demand that the education sector, including Muhammadiyah, integrate technological sophistication with Islamic ethical values. This paper examines the thoughts of KH Ahmad Dahlan within the framework of Muhammadiyah’s educational philosophy in responding to the challenges of digitalization and digital literacy. Using a qualitative literature study approach, the discussion focuses on the concept of tauhidic ethics an ethical foundation rooted in the oneness of God (tauhid) and its application in fostering digital civility. This concept is compared with the ideas of Syed M. Naquib Al-Attas on adab, Seyyed Hossein Nasr on spirituality and technology, Paulo Freire on critical literacy, and Mike Ribble on digital citizenship. The study shows that tauhidic ethics is relevant in shaping ethical digital behavior, in line with Al-Attas’ emphasis on the proper placement of knowledge, and Nasr’s view on the importance of spiritual dimensions in the use of modern technology. Freire contributes a critical awareness perspective that aligns with the Islamic principle of tabayyun (verification), while Ribble offers practical guidelines that can be integrated with Muhammadiyah values such as the Akhlaq Sosmediyah movement. Therefore, Muhammadiyah